Mycotoxins: Biotransformation and Bioavailability Assessment Using Caco-2 Cell Monolayer - Tran, Van Nguyen; Viktorová, Jitka; Ruml, Tomáš (Toxins, 2020)
The determination of mycotoxins content in food is not sufficient for the prediction of their potential in vivo cytotoxicity because it does not reflect their bioavailability and mutual interactions within complex matrices, which may significantly alter the toxic effects. Moreover, many mycotoxins undergo biotransformation and metabolization during the intestinal absorption process. Biotransformation is predominantly the conversion of mycotoxins meditated by cytochrome P450 and other enzymes. This should transform the toxins to nontoxic metabolites but it may possibly result in unexpectedly high toxicity. Therefore, the verification of biotransformation and bioavailability provides valuable information to correctly interpret occurrence data and biomonitoring results. Among all of the methods available, the in vitro models using monolayer formed by epithelial cells from the human colon (Caco-2 cell) have been extensively used for evaluating the permeability, bioavailability, intestinal transport, and metabolism of toxic and biologically active compounds. Here, the strengths and limitations of both in vivo and in vitro techniques used to determine bioavailability are reviewed, along with current detailed data about biotransformation of mycotoxins. Furthermore, the molecular mechanism of mycotoxin effects is also discussed regarding the disorder of intestinal barrier integrity induced by mycotoxins.
Keywords: metabolická aktivace; permeabilita; hodnocení rizik; Mycotoxins; mycotoxins; Risk Assessment; epitelové buňky; Inactivation, Metabolic; cytochrome; Epithelial Cells; metabolická inaktivace; střevní sliznice; intestinální absorpce; permeability; bioavailability; metabolism; Permeability; biologická dostupnost; lidé; Humans; Caco-2 Cells; Intestinal Mucosa; Caco-2 buňky; Intestinal Absorption; Biological Availability; intestinal transport; Activation, Metabolic; biotransformation; mykotoxiny